PHYSICAL MODELING OF THE PROCESS OF OIL FLOW THROUGH THE RESERVOIR SANDSTONE ROCK SAMPLES IN THE RESERVOIR CONDITIONS (ROZUMIVSKE GAS CONDENSATE FIELD) - VYZHVA, Serhii; VENGROVICH, Dmytro; ONYSHCHUK, Viktor; ONYSHCHUK, Ivan; DATSENKO, Anna (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. In the article the results of the physical modeling of oil flow through the reservoir rocks are described. In petrophysical laboratory sandstones of Rozumivske gas condensate field were studied. The aim of the research was to probe into petrophysical parameters of core samples of sandstones and the physical modeling of oil flow through them in reservoir conditions.Methods. Standard methods were performed to determine petrophysical parameters (density, porosity, the structure of void space, permeability) of sandstone samples in atmospheric conditions. The high-pressure installation was applied for physical modeling of the process of oil flow through the sandstone samples.Results. The reservoir (flow) properties of sandstone samples in atmospheric conditions and in the physical modeling of reservoir conditions are investigated. The values of the reservoir parameters of the studied rocks and their comparison are given. The structure of the void space of rocks and its analysis was evaluated. The results of studies of permeability of rocks for oil in different pressure-temperature conditions are presented.Conclusions. Via correlation analysis a number of correlations between the permeability of samples and the temperature and pressure in the reservoir conditions were established. These correlations can be used in the interpretation of geophysical studies of wells and modeling of reservoirs parameters of rocks. Then, the results of this research are going to be at the basis for studying the effect of vibro-wave and chemical methods on the filtration properties of such reservoirs in order to intensify hydrocarbon production.
Keywords: sandstones; reservoir parameters; density; porosity, permeability and residual water saturation factor; structure of void space; reservoir conditions; correlations